Energy transfer of intrinsic electronic excitation to impurities in the CaSO4-Mn system - Nurakhmetov, T; Tolekov, D.A.; Alibay, T.T.; Yussupbekova, B.N.; B.M. Sadykova, B.M. Sadykova; Azmagambetova, Zh.; Daurenbekov, D.H.; Kainarbay, A. Zh.; Zhunusbekov, A. M.; Zhangylyssov, K. B.; Salikhodzha, Zh. M.; Tulebayeva, N. (Eurasian Journal of Physics and Functional Materials, 2026)
The nature of the impurity emission center and the energy transfer mechanisms from intrinsic electronic excitations to the Mn2+ impurity centers in the CaSO4 . Mn crystal have been investigated. The methods of vacuum ultraviolet, atomic absorption and luminescence spectroscopy are used in a wide temperature range from 5 K to 300 K. The energy transfer of intrinsic electronic excitations to impurity emission centers in CaSO4 . Mn has been detected.Recommended CitationNurakhmetov, T. N.; Salikhodzha, Zh. M.; Zhangylyssov, K. B.; Zhunusbekov, A. M.; Kainarbay, A. Zh.; Daurenbekov, D. H.; Azmagambetova, Zh.; Sadykova, B. M.; Yussupbekova, B. N.; Alibay, T. T.; Tolekov, D. A.; and Tulebayeva, N. (2021) "Energy transfer of intrinsic electronic excitation to impurities in the CaSO4-Mn system," Eurasian Journal of Physics and Functional Materials: Vol. 5: No. 1, Article 4.DOI: https://doi.org/10.32523/ejpfm.2021050104